La citoyenneté au travail ? Une introduction = Towards Citizenship at Work? An Introduction - Coutu, Michel; Murray, Gregor (Relations industrielles / Industrial Relations, 2005)
Editorial introduction to the issue.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z